EVALUASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT GASING SULAWESI - Jasrani Jasrani; Arafat Arafat; Firdaus Firdaus (LPPM Universitas Madako Tolitoli, 2023)
This article evaluates the implementation of Corporate Social Responsibility (CSR) or social responsibility of PT Gasing Sulawesi, a mining company C in its operational area, Oko-Oko Village, Pomalaa District, Kolaka Regency, Southeast Sulawesi. The research conducted is qualitative. Primary data collection through observation to interviews in April-May 2022 in Oko-Oko Village with eight informants using purposive sampling, namely two informants from PT Gasing Sulawesi, the village head, village secretary, and the head of Oko-Oko village representative body and three informants from the community benefit recipients. The research results are in four indicators. On the input indicator, CSR assistance with village operations is higher (60%) than the needs of the village community (40%). On the process indicator, PT Gasing assists in stages every year based on the village government's report. On the output indicator, the village government used CSR to realize physical development in the form of a mosque, village roads, procurement of electricity meters, and house renovation but has not yet touched on educational scholarships. As for the impact indicator, considered is not evenly distributed across all layers or social groups, especially vulnerable communities.